ANTIBACTERIAL ACTIVITY TEST OF BAY LEAF EXTRACTS (SYZYGIUM POLYANTHUM (WIGHT) WALP.) AGAINST STAPHYLOCOCCUS AUREUS AND ESCHERICHIA COLI: SYSTEMATIC LITERATURE REVIEW - Gladys Imanda Sapoetri; Rika Revina; Annisa Farida Muti (Journal of Research in Pharmacy and Pharmaceutical Sciences, 2022)
Antibiotic resistance is a global health problem that has severe implications for morbidity, mortality, and health costs. Based on the Antimicrobial Resistant in Indonesia (AMRIN-Study), it was reported that there were bacteria that were resistant to antibiotics, including Escherichia coli, which is resistant to ampicillin trimethoprim-sulfamethoxazole and ciprofloxacin; and Staphylococcus aureus which is resistant to oxacillin, vancomycin, clindamycin, and levofloxacin. In Indonesia, Syzygium polyanthum (Wight) Walp. Bay leaf is one of the plants that is often used as spices. Its bay leaf contains secondary metabolites that have an antibacterial function. This study analyzed the antibacterial activities of bay leaf extract against Staphylococcus aureus and Escherichia coli. This research used a systematic literature review with a literature search strategy using Google Scholar and PubMed. The literature discusses bay leaf extract, Staphylococcus aureus, Escherichia coli, and antibacterial activity. From this study, 14 research articles described the antibacterial activity of bay leaf extract by inhibiting the growth of Staphylococcus aureus and Escherichia coli in the medium, strong, and very strong categories. Bay leaf extract can inhibit the growth of Staphylococcus aureus and Escherichia coli because it contains phytochemical compounds with antibacterial properties, including alkaloids, flavonoids, steroids/ triterpenoids, saponins, tannins, phenols, essential oils, and carbohydrate.